EXPEDIENT PROTOCOL FOR THE INSTALLATION OF THIADIAZOLE ON 2-POSITION OF 1,4-BENZODIAZEPIN-5-CARBOXAMIDE THROUGH A PHENOXYL SPACER - NAVJEET KAUR (International Journal of Pharma and Bio Sciences, 2013)
An efficient novel single step strategy for the heteroannulation of 2-chloro-1,4-benzodiazepine ring, substituted in its 5-position with a carboxamido group (5), has been developed to allow the easy installation of thiadiazole (8) ring through thiosemicarbazone (7) intermediate. In this communication, exceedingly facile single step expedient protocols based on the versatility and reactivity of corresponding intermediate thiosemicarbazone (7), derived from 5-carboxamido-1,4-benzodiazepin-5-(4’-methylpiperazinyl)-carboxamide (5) have been developed to provide an easy installation of the thiadiazole (8) privileged template at 2-position of 5-carboxamido-1,4-benzodiazepin-5-(4’-methylpiperazinyl)-carboxamide, through a phenoxyl spacer.